2020
DOI: 10.3390/w12082247
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change Impacts on Soil Erosion and Sediment Yield in a Watershed

Abstract: This study analyzed the influence of climate change on sediment yield variation, sediment transport and erosion deposition distribution at the watershed scale. The study was based on Gaoping River basin, which is among the largest basins in southern Taiwan. To carry out this analysis, the Physiographic Soil Erosion Deposition (PSED) model was utilized. Model results showed a general increase in soil erosion and deposition volume under the A1B-S climate change scenario. The situation is even worsened with incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 25 publications
0
8
0
1
Order By: Relevance
“…Additionally, Chen et al [28] analyzed the influence of climate change on sediment yield variation, sediment transport, and erosion deposition distribution in the Gaoping river basin, a southern watershed of Taiwan. They concluded that future climate change variability would influence the watershed through increased sediment yields, even worsening the impacts of natural disasters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, Chen et al [28] analyzed the influence of climate change on sediment yield variation, sediment transport, and erosion deposition distribution in the Gaoping river basin, a southern watershed of Taiwan. They concluded that future climate change variability would influence the watershed through increased sediment yields, even worsening the impacts of natural disasters.…”
Section: Discussionmentioning
confidence: 99%
“…Almost all extreme climate occasions are related to water-based situations. For instance, heavy rainfall events have become more frequent and concentrated, leading to disasters such as landslides and debris flow in many watersheds locating at the upstream area, which have seriously affected the safety of the people [26][27][28]. In August 2009, Typhoon Morakot brought record-breaking heavy rainfall to the upstream watershed in southwestern and southeastern Taiwan.…”
Section: Introductionmentioning
confidence: 99%
“…Nesse estudo observa-se o aumento da perda de solos, contudo sem um aumento expressivo para a década de 2090. Chen et al (2020) também realizaram pesquisa para uma bacia hidrográfica asiática, sendo o rio Gaoping o foco de estudo, que está entre os maiores do sul de Taiwan. O volume total de sedimentos estimados para a bacia hidrográfica sob o cenário A1B-S para vários períodos de retorno aumentaria de 4 a 65%, apresentando períodos de retorno de 2 a 200 anos.…”
Section: Methodsunclassified
“…These changes can interfere with the quantity and intensity of rainfalls, directly interacting with watershed erosion [Chen et al 2020]. This can lead to severe erosion in some areas and in a decrease of the phenomena in others.…”
Section: Introductionmentioning
confidence: 99%